2011
DOI: 10.1085/jgp.201010591
|View full text |Cite
|
Sign up to set email alerts
|

D4cpv-calsequestrin: a sensitive ratiometric biosensor accurately targeted to the calcium store of skeletal muscle

Abstract: Current fluorescent monitors of free [Ca2+] in the sarcoplasmic reticulum (SR) of skeletal muscle cells are of limited quantitative value. They provide either a nonratio signal that is difficult to calibrate and is not specific or, in the case of Forster resonant energy transfer (FRET) biosensors, a signal of small dynamic range, which may be degraded further by imperfect targeting and interference from endogenous ligands of calsequestrin. We describe a novel tool that uses the cameleon D4cpv, which has a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 48 publications
8
65
0
Order By: Relevance
“…2B shows a raw confocal image of the fluorescence of Casq1 fused with EYFP in cells of a calsequestrin-null mouse. EYFP-Casq1 fluorescence forms two bands per sarcomere, consistent with the location previously found for native Casq1 (23), and for Casq1 fused with D4cpV (24). The agreement indicates that Casq1 fused to either tag traffics in the same way as native Casq1, to SR terminal cisternae (TC).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…2B shows a raw confocal image of the fluorescence of Casq1 fused with EYFP in cells of a calsequestrin-null mouse. EYFP-Casq1 fluorescence forms two bands per sarcomere, consistent with the location previously found for native Casq1 (23), and for Casq1 fused with D4cpV (24). The agreement indicates that Casq1 fused to either tag traffics in the same way as native Casq1, to SR terminal cisternae (TC).…”
Section: Resultssupporting
confidence: 87%
“…4C is a 3D rendering of the deblurred stack. The images confirm the observation (24) that in cells at rest, D4cpv-tagged Casq1 resides mostly in two bands per sarcomere. Fluorescence costaining (23,24) has shown that the bands correspond to triads, each with two TC not resolved in these images.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding the data obtained at 22 [19] to near 1 mM [20], with most of the obtained figures around 400-800 M [21][22][23][24][25][26][27]. On the other hand, NMR measurements [21], skeletal muscle cells [25,27] and rabbit heart cells [28] The new probe has also a very important technical and experimental advantage over the previous aequorin probes. All the [Ca 2+ ] ER measurements carried out before with these probes were performed in cells previously depleted of Ca 2+ , because the high Ca 2+ content of the ER precluded reconstitution with the coelenterazine cofactor.…”
Section: Discussionmentioning
confidence: 90%